Simultaneous quantitation of loganin and sweroside in plasma using column-switching high-performance liquid chromatography - Son, J; Lee, J; Han, CK; Kwak, WJ; Yang, R; Kim, DH (ELSEVIER SCIENCE BV, 2004)
A column-switching high-performance liquid chromatography (HPLC) method is described for the simultaneous determination of loganin and sweroside, which are the active ingredients of purified herbal extract from Lonicera japonica (SKL JI), in rat plasma using column-switching and ultraviolet (U-V) absorbance detection. Plasma was simply filtrated prior to injection to the HPLC system consisting of a clean-up column, a concentrating column, and an analytical column, which were connected with two six-port switching valves. Detection of loganin and sweroside was accurate and repeatable, with a limit of quantitation of 0.05 mug ml(-1) in plasma. The calibration curves for both loganin and sweroside were linear over the concentration ranges of 0.05-40.0 and 0.02-40.0 mug ml(-1) in rat plasma, respectively. The intra- and inter-day precision over the concentration range for loganin and sweroside were lower than 8.1 and 10.9% (relative standard deviation, R.S.D.), and accuracy was between 94.7 and 113.5 and 95.0 and 113.1%, respectively. This method has been successfully applied to determine the levels of loganin and sweroside in rat plasma samples from pharmacokinetics studies. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: SECOIRIDOID GLYCOSIDES; DIRECT-INJECTION; LIVER-INJURY; MICE